(untitled) (London, 2002)
This book covers some of the most recent advances in gynaecological surgery technique and practice. It has been written by some of the leading names in the field, from the UK, Europe and USA, each chapter representing a concise distillation of the most up-to-date information available on that particular topic. Each chapter is fully illustrated, in colour where necessary.
Keywords: Generative organs, Female,Cơ quan sinh sản, Nữ,Laparoscopic surgery,Phẫu thuật nội soi; Surgery,Phẫu thuật